2018
DOI: 10.1002/cnma.201800147
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Based Self‐assembled Nanostructures: Complex Structures from Remarkably Simple Building Blocks

Abstract: Amino acids are the simplest biological building blocks capable of forming discreet nanostructures by supramolecular self-assembly. The understanding of the process of organization of amino acid nanostructures is of fundamental importance for the study of metabolic diseases as well as for materials science applications. Although peptide self-assembled structures have been the topic of many review articles, much less attention has been devoted to the ability of amino acid building blocks, both natural and synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 81 publications
0
77
1
Order By: Relevance
“…[11b] This wide diversity of morphologies from amino acid based self-assembled materials has been recently pointed out in the literature. [24] Furthermore, in the attempt to relate morphology to T gel and mechanical strength, we observed that, higher T gel values and stronger gel phases were featured by the presence of spheroidal structures in the gelatinous network.…”
Section: Resultsmentioning
confidence: 89%
“…[11b] This wide diversity of morphologies from amino acid based self-assembled materials has been recently pointed out in the literature. [24] Furthermore, in the attempt to relate morphology to T gel and mechanical strength, we observed that, higher T gel values and stronger gel phases were featured by the presence of spheroidal structures in the gelatinous network.…”
Section: Resultsmentioning
confidence: 89%
“…Self-assembled nanogels were firstly introduced by Akiyoshi and colleagues, where hydrophilic pullulan polysaccharides were conjugated with hydrophobic cholesterol units and sonication of these amphiphilic polysaccharide derivatives in water yielded intramolecularly self-aggregated monodisperse particles with 25±5 nm sizes [22]. Moreover numerous microgels and nanogels have been reported by self-assembly process including synthetic and natural polymeric substrates such as poly(Nisopropylacrylamide) (PNIPAM) [23], poly(hydroxyethyl methacrylate) (p(HEMA)) [24], polysaccharides [25], pullulan [26], chitosan (CHI) [27][28][29][30][31][32], alginic acid [24], dextran [33,34], hyaluronic acid (HA) [35][36][37][38][39], starch derivatives [40], and polyphenols [41][42][43][44], proteins [45], polypeptides [46,47], various amino acids [48], and DNA [30,49,50] all of which were intended for biomedical applications in delivery of various therapeutic agents including small molecules, proteins, drugs, and genes and siRNAs.…”
Section: Physically Crosslinked Microgels and Nanogelsmentioning
confidence: 99%
“…Amino acids show different physicochemical properties and self‐assembling propensity depending on the charge, hydrophobicity or size of their side chain, allowing the engineering of the desired assembly . As a result, the morphologies that peptides can form upon assembly are diverse and include fibers, vesicles, nanobelts, nanotubes or colloids among others . Moreover, in recent years, design rules for the self‐assembly of peptides have become available .…”
Section: Self‐assembly Of Peptidesmentioning
confidence: 99%
“…[5] As a result, the morphologies that peptides can form upon assembly are diverse and include fibers, [6] vesicles, [7] nanobelts, [8] nanotubes [9] or colloids [10] among others. [11,12] Moreover, in recent years, design rules for the selfassembly of peptides have become available. [5] The wide range of assemblies from relatively simple building block demonstrates the power of peptides to design complex nanostructures from the bottom up.…”
Section: Introductionmentioning
confidence: 99%